Optimalisasi Hubungan Bisnis untuk Ekspansi Pasar Internasional UMKM Batik Giriloyo Kabupaten Bantul, Yogyakarta - Heri Prabowo; Hawik Ervina Indiworo; Qristin Violinda; Bayu Kurniawan; Ika Menarianti; Rita Meiriyanti; Fithri Widyannita Yarisma; Ratih Hesty Utami; Shofif Sobaruddin Akbar; Chadiyan Faturachman; Farah Chalida Hanoum (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Optimizing international marketing strategies is a significant challenge faced by Micro, Small, and Medium Enterprises (MSMEs), including Batik Giriloyo business actors in Bantul Regency, Yogyakarta, in an effort to expand global market penetration. Various obstacles such as limited access to international markets, minimal use of digital technology for marketing, and weak cross-country cooperation networks are the main obstacles in business expansion. To overcome these problems, an empowerment program has been implemented which includes creating an e-commerce account through the Shopify platform and holding an international webinar entitled "Penetrating the Global Market: Batik Giriloyo's Successful Strategy in the International Arena" as a means of increasing promotion and global business networks. The program implementation method includes intensive training in the use of digital technology, global marketing strategies, and cross-cultural communication, which significantly increases brand visibility and forms partnerships with international resellers. The results of the activity show that the integration of digital technology in a marketing strategy based on local cultural values ​​is able to provide strong competitive differentiation for MSMEs, especially in the context of preserving the cultural heritage of batik as the identity of a superior product. As a form of follow-up, it is recommended to strengthen digital training, increase strategic collaboration with international partners, and develop marketing strategies that highlight local wisdom values, in line with the implementation of the Tri Dharma of Higher Education in the aspect of community service.